Molecular epidemiology of β-lactamase production in penicillin-susceptible Staphylococcus aureus under high-susceptibility conditions. Issue 2 (February 2018) - Matono, Takashi; Nagashima, Maki; Mezaki, Kazuhisa; Motohashi, Ayano; Kutsuna, Satoshi; Hayakawa, Kayoko; Ohmagari, Norio; Kaku, Mitsuo
Abstract: Little is known about the prevalence of β-lactamase production in penicillin-susceptible Staphylococcus aureus isolates under high-susceptibility conditions. We analyzed S. aureus isolates with penicillin G minimum inhibitory concentration (MIC) ≤ 0.12 μg/ml that were recovered from in-/outpatients (n = 108) between 2016 and 2017 in Japan. β-Lactamase production was detected by nitrocefin-based and Clinical and Laboratory Standards Institute penicillin zone edge testing and blaZ PCR. All isolates were categorized as having penicillin G MIC ≤0.03 μg/ml using an automated system; MICs determined based on the microdilution method were 0.016 μg/ml (2%), 0.03 μg/ml (44%), and 0.06 μg/ml (54%). Notably, no isolates harbored the blaZ gene. The results from the nitrocefin-based and zone edge tests were consistent with those obtained by PCR. S. aureus isolates with penicillin G MIC ≤0.03 μg/ml exhibited a low frequency of β-lactamase production. Thus, screening for β-lactamase production may be unnecessary for isolates showing such high susceptibility.